Estudio de factibilidad para la creación de la cafetería gourmet Melek Pastry, Ibarra, Ecuador, 2025-2029 - Coello Armas, María Mercedes (2024)
The feasibility study for the creation of the gourmet café Melek Pastry in the city of Ibarra was conducted with the aim of performing a comprehensive analysis of the local market, determining the technical and financial requirements for implementing the business, and evaluating its potential profitability. An exploratory and descriptive methodology was employed, including conducting surveys of the target population and statistical analysis of the obtained data. The results revealed an unmet demand in the local market, ensuring the project's viability, and demonstrated a positive return on investment over five years of operation. It was concluded that the Melek Pastry café is a viable and profitable business, supported by financial indicators such as a positive NPV and an IRR exceeding the cost of capital.